A Mechanistic Approach to Replacing Antibiotics with Natural Products in the Treatment of Bacterial Diarrhea - Mingbang Wei; Huaizhi Liu; Zhefan Hu; Peixiao Wen; Yourong Ye; Yangzom Chamba; Hongliang Zhang; Peng Shang (Biomolecules)
Natural products have emerged as potential alternatives to antibiotics in the treatment of bacterial diarrhea, due to their multi-targeting effects, low potential for inducing resistance, and favorable safety profiles. Currently, the search for natural product-based therapies has become an emerging focus in medical research. This growing interest is driven by the increasing awareness that the widespread and irrational use of antibiotics has contributed to the alarming rise in antibiotic-resistant bacterial strains, which in turn diminishes the efficacy of conventional drugs. Among these concerns, the limitations of antibiotics in managing bacterial diarrhea and the potential mechanisms by which natural products exert therapeutic effects are the main focus of this paper. Natural products, containing a wide array of bioactive compounds, can not only directly inhibit the growth of pathogenic bacteria, disrupt bacterial membrane synthesis, and reduce toxin production, but also modulate inflammatory responses, enhance immune function, repair intestinal barriers, and restore gut microbial ecology—highlighting their systemic and multi-targeted therapeutic potential. Therefore, this paper will elaborate on how natural products combat bacterial diarrhea from three aspects: the pathogen and pathogenesis of bacterial diarrhea, natural product-based therapeutic studies, and the underlying mechanisms of action, thereby proposing natural products as viable alternatives to antibiotics.